2011
DOI: 10.1002/jssc.201100361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process parameters on supercritical CO2 extraction of total phenols from strawberry (Arbutus unedo L.) fruits: An optimization study

Abstract: The aim of this work was to optimize total phenolic yield of Arbutus unedo fruits using supercritical fluid extraction. A Box-Behnken statistical design was used to evaluate the effect of various values of pressure (50-300 bar), temperature (30-80°C) and concentration of ethanol as co-solvent (0-20%) by CO2 flow rate of 15 g/min for 60 min. The most effective variable was co-solvent ratio (p<0.005). Evaluative criteria for both dependent variables (total phenols and radical scavenging activity) in the model we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 17 publications
3
19
0
1
Order By: Relevance
“…, ; Akay et al. ; Pieszka et al. ) For walnut husk extraction, an extensive literature review reveals that investigators commonly dry the walnut husks at various temperatures prior to extraction, Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, ; Akay et al. ; Pieszka et al. ) For walnut husk extraction, an extensive literature review reveals that investigators commonly dry the walnut husks at various temperatures prior to extraction, Table .…”
Section: Resultsmentioning
confidence: 99%
“…(Pohler and Kiran 1997) A similar increase in antioxidant potential and total phenolic content was also observed in the supercritical carbon dioxide extraction of both strawberries and grape seeds as ethanol content increased from 0 to 20%. (Murga et al 2000;Akay et al 2011) For both TPC and FRAP analysis, the highest antioxidant potential was observed at an extraction condition of 68°C with 20 wt-% ethanol. It may be possible that even higher temperatures and ethanol content can result in higher antioxidant potential extractions, however, there are practical concerns as more extreme conditions are reached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the influence of temperature and pressure on the extraction process of bioactive substances gave different results due to the plant materials and targeted compounds [ 40 , 42 , 44 , 45 , 46 , 47 , 48 ]. For example, high pressures were reported to enhance the global extraction yield of phenolic compounds [ 40 , 45 , 47 ], while Akay et al [ 46 ] reported a high total phenolic content under low pressure and no significant difference to the yield when increasing temperature and pressure. Some results showed that an augmentation in the recovery of phenolic compounds could be obtained by reducing the extraction temperature and increasing the addition of co-solvent and pressure [ 45 ].…”
Section: Parameters To Consider and Their Effect During Supercritimentioning
confidence: 99%
“…The extracts of A. unedo fruits revealed to have in vitro antioxidant activity [26,29,36,37,40,58,59,60,61,62]. The type of extraction of phenols present in fruits of A. unedo influenced the antioxidant activity.…”
Section: Biological Properties and Applicationsmentioning
confidence: 99%